An epidemiological study of 500 paediatric burn patients in Mumbai, India - S S Verma; S Srinivasan; A M Vartak (Indian Journal of Plastic Surgery, 2007)
Aim: To study the epidemiological data of paediatric burn patients to determine the role of demographic distribution and epidemiological parameters for assessment of mortality rate and development of burn prevention strategy.Materials and methods : epidemiological data of 500 patients admitted to the burns and plastic surgery unit of b.j. wadia hospital, mumbai over a period of six years (2000-2005) was reviewed from medical records. age, sex, demographic distribution, seasonal variation, total body surface area (tbsa) involved, type and place of burn injury, parental occupation, family size, first aid and mortality rate were studied.Result: Median age group for patient was 3.44 years (range one month to 14 years). the majority (24%) of burns occurred in children between the one to two years age group. male to female sex ratio was 1.38:1. most of the patients were from the defined demographic region served by the hospital. a significant number of patients however were from outside this region. burn injury occurred predominantly during winter. most common type of burn was scalds which occurred mainly in domestic circumstances. in the majority of patients, less than 10% tbsa was involved. all patients were managed as per the unit protocol. mortality rate was 10.4%. mortality rate was high in patients having more than 40% tbsa involvement. seventy-three per cent of the total deaths occurred in the patients coming from regions outside the demographic region served by the hospital. parental occupation, family size and the first aid did not affect the mortality rate.Conclusion: Availability of a burn care unit in the vicinity can decrease the mortality rates in the paediatric burn patients. an intense and focused burn prevention campaign to educate the general population about dangerous aetiological factors will decrease the incidence of paediatric burns.